Pengaruh Model Discovery Learning Terhadap Hasil Belajar Matematika Peserta Didik Kelas VIII SMP Negeri 1 Siak Hulu - Ainirohmah, Nailu; Indriati, Mefa; Angraini, Lilis Marina; Herlina, Sari (Polinomial : Jurnal Pendidikan Matematika, 2025)
This study aims to determine the effect of the Discovery Learning model on the mathematics learning outcomes of class VIII students at SMP Negeri 1 Siak Hulu in the 2025/2026 academic year. This study uses a quantitative approach. The type used is quasi-experimental research. This experiment is called a quasi-experiment. The population in this study were all students of class VIII of SMP Negeri 1 Siak Hulu in the academic year of 2026. Sampling in this study used a purposive sampling technique by selecting two classes, namely class VIII B as the experimental class and class VIII A as the control class. The original plan for the type of sample for the experimental class and the control class was 34 and 35 students, respectively. However, during the implementation there were students who were absent, so the sample for the experimental class was 32 students and the sample for the control class was 26 students. The research instruments used in this study were pre-test and post-test essay questions to determine student learning outcomes. The data analysis techniques used are descriptive analysis and inferential analysis. Based on the results of the research and the results of the research data analysis that have been carried out, the value of Asymp.Sig (2-tailed) <α was obtained with α = 0.05 and Asymp.Sig (2-tailed) = 0.000 (0.000 <0.05). Therefore, H_0 is rejected and H_1 is accepted, meaning there is a difference between the average learning outcomes of students in the experimental class and the control class. So it can be concluded that there is an influence of the discovery learning model on the mathematics learning outcomes of class VIII students at SMP Negeri 1 Siak Hulu.